Knowledge, dexterity, and attention : a theory of epistemic agency - Fairweather, Abrol (Cambridge University Press, 2017)
Contemporary cognitive science clearly tells us that attention is modulated for speech and action. While these forms of goal-directed attention are very well researched in psychology, they have not been sufficiently studied by epistemologists. In this book, Abrol Fairweather and Carlos Montemayor develop and defend a theory of epistemic achievements that requires the manifestation of cognitive agency. They examine empirical work on the psychology of attention and assertion, and use it to ground a normative theory of epistemic achievements and virtues. The resulting study is the first sustained naturalized virtue epistemology, and will be of interest to readers in epistemology, cognitive science, and beyond.